Jobless Growth di Kawasan Industri Kabupaten Sidoarjo: Analisis Autoregressive Distributed Lag (ARDL) Bounds Testing - Suprianto Suprianto; Kisfendie Regga Rahmad Igarta; Adzra Aniqoh (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Manufacturing is a dominant economic sector, yet high sectoral contribution and investment do not always translate into proportional labor absorption. Specific Background: In Sidoarjo Regency, the manufacturing sector contributes strongly to regional economic output and receives substantial investment, but labor absorption remains below expectations. Knowledge Gap: Previous studies on labor absorption in Indonesia have mostly used cross-section, panel, or broader regional approaches, leaving limited time-series evidence on short-run and long-run relationships at the district level. Aims: This study aims to explain the short-run and long-run relationships between manufacturing labor absorption as the dependent variable and value added and investment as independent variables using the Autoregressive Distributed Lag approach for 2010-2024 data. Results: In the short run, value added and investment showed positive relationships with labor absorption, with a coefficient of 1.005. In the long run, although statistically insignificant, value added recorded a coefficient of -0.21 and investment -0.12, indicating declining labor absorption consistent with jobless growth. The error correction term was -0.45 per year. Novelty: The study offers district-level ARDL evidence on industrial labor absorption by distinguishing short-run gains from long-run jobless growth tendencies. Implications: The findings suggest that industrial investment policy should pay attention to whether capital formation supports employment or mainly reinforces automation that replaces labor. Highlights: Value added and capital formation showed positive short-run coefficients. Long-run coefficients for output and funding were negative but statistically nonsignificant. ECT indicated annual adjustment toward equilibrium at minus 0.45. Keywords: Manufacturing Labor Absorption, Autoregressive Distributed Lag (ARDL), Jobless Growth